Regional economic integration: Africa's challenges for the 1990s - Kiggundu, Suleiman (Dr.) (Kampala: Bank of Uganda, 1990)
The Third Joseph Mubiru memorial lecture, Kampala International Conf erence Centre (Monday, October 8th, 1990)
Keywords: International economic integration